2007
DOI: 10.1295/polymj.pj2007067
|View full text |Cite
|
Sign up to set email alerts
|

Dewetting Inhibition and Interfacial Structures of Silsesquioxane-terminated Polystyrene Thin Films

Abstract: ABSTRACT:Polyhedral oligomeric silsesquioxane (POSS)-terminated polystyrene (PS-POSS) was prepared by nitroxide-mediated radical polymerization of styrene with POSS-containing initiator, and the thermal stability of PS-POSS thin films was investigated. Rheological measurement of PS-POSS revealed that the rheological properties were profoundly affected by the presence of POSS end groups in low molecular weight region (M n % 2000), while those were nearly unaffected in high molecular weight region (M n %

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Miyamoto et al [7]. They studied the structure of PS-POSS thin films by the neutron reflectivity measurements of deuterated PS-POSS thin films, and they found that the POSS moieties of dPS-POSS formed an enrichment layer at the surface and the substrate interface.…”
Section: A Static Structure Of Ps-poss Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Miyamoto et al [7]. They studied the structure of PS-POSS thin films by the neutron reflectivity measurements of deuterated PS-POSS thin films, and they found that the POSS moieties of dPS-POSS formed an enrichment layer at the surface and the substrate interface.…”
Section: A Static Structure Of Ps-poss Thin Filmsmentioning
confidence: 99%
“…This manuscript version is made available under the Elsevier user license http://www.elsevier.com/open-access/userlicense/1.0/ also observed the inhibition of dewetting using octacyclopentyl-POSS-terminated PS thin films (PS-POSS) [7]. Miyamoto et al found that the low molecular weight PS-POSS (M n  2000) produced a large difference in the dewetting behavior, whereas the high molecular weight analog (M n  40,000) produced a small difference [7]. They investigated the structures of thin films by neutron reflectivity measurements, and discussed the suppression of dewetting in terms of the segregation of POSS at the surface and at the substrate interface.…”
Section: Introductionmentioning
confidence: 95%
“…In literature, there are several approaches to improve the stability of polymer films in spin coating by strengthening the interaction between polymer and substrate, which can be realized either through the modifications of substrates or through the functionalization of polymer end groups . Recently, it has been reported that the dewetting of spin‐coated polymer films can be retarded by the addition of various nanofillers, such as fullerence , carbon black , carbon nanotubes , star polymer , hyperbranched polymer , dendrimers , polymer nanoparticles , metal nanopaticles , silicon nanoparticles , quantum dots , polyhedral oligomeric silsesquioxanes with various substituents , etc.…”
Section: Introductionmentioning
confidence: 99%
“…By modifying the interfacial tension between film and substrate, the stability of polymeric thin film is improved. [8][9][10][11][12][13][14][15][16][17][18][19][20] For example, the substrate surface is modified by chemical compositions with high affinity to the polymer film. 10 Thus, the interfacial tension between film and substrate is attuned, which improves the stability of polymeric thin film.…”
Section: Introductionmentioning
confidence: 99%
“…Functionalized polymers with adherent groups can segregate to the solid substrate. [11][12][13][14][15][16]18,19,21 Therefore, the addition of functionalized polymers such as sulfonated polystyrene with a sulfonation level of 0.76-6.5 mol% or poly(styrene-stat-chloromethylstyrene) with 5 mol% of chloromethylstyrene group into polystyrene (PS) thin film can enhance interfacial interactions, which in turn retard the dewetting process. 12,13,15,16 A fascinating strategy to suppress the dewetting of polymeric thin films is also presented by Barnes et al 22 The addition of small amounts of fullerene nanoparticles into PS and polybutadiene thin films results in significant enhancement of their stability.…”
Section: Introductionmentioning
confidence: 99%